Do local leaders know their voters? A test of guessability in India. (October 2019) - Schneider, Mark
Abstract: Prominent theories of clientelism—the exchange of benefits for political support—depend on the assumption that politicians, through local agents immersed in local social networks, possess detailed information on voters' political preferences prior to targeting. This article provides the first direct test of this assumption. It develops a behavioral measure, guessability, which gauges the ability of elected village leaders, who often function as brokers and prominent vote mobilizers, to correctly identify the partisan vote intentions of voters in their locality. It then develops a method to estimate added informational value, which compares the performance of local leaders to low-information benchmarks that capture guessability rates that can feasibly be achieved by outsiders. Original data from surveys of voters and elected village politicians across 96 village councils in Rajasthan, India indicate that while these village leaders out-perform low-information benchmarks with respect to co-partisans, they perform no better than this baseline vis-à-vis non-co-partisans.